Transformation strategies in community engagement: Selected initiatives by Malaysian libraries. (June 2018) - Baba, Zawiyah; Abrizah, A.
This paper examines initiatives developed in Malaysian libraries to enhance library roles in promoting knowledge and technology exchange as well as community wellbeing. It explores how libraries in Malaysia are transforming society through community engagement and highlights initiatives undertaken by libraries that promote community access to collections, services, and events. The success of the initiatives is demonstrated in seven transformation strategy themes, namely; (i) embedded services; (ii) bridges and web technology; (iii) strategic and institutional partnering; (iv) rural libraries; (v) community libraries; (vi) asset-based community development; and (vii) international librarianship. While it is often cited that public libraries are those that serve the community at large, this paper provides the perspective from other types of library viewpoints, emphasizing that such community outreach services should not be limited to public libraries. The library science community at large, and especially academic libraries, must play a role in community engagement.